An inventory model for deteriorating items with partial backlogging using linear demand in fuzzy environment - Neeraj Kumar; Sanjey Kumar (Cogent Business & Management, 2017)
This model presents the invention scheduling difficulty in industry with different operational constraints, as well as strategic plan of the business, revenue purpose, and limit on finishing. In this article, we have studied an inventory model for deteriorating items with shortages under partially backlogging. The aim of present study is to minimize the total cost function in fuzzy environment. Graded mean representation, signed distance, and centroid methods are used to defuzzify the total cost function over the planning horizon. Further, all costs are defuzzified with the help of triangular fuzzy numbers. Finally, sensitivity analysis is also given to show the effect of the costs.